Comparison of the Effectiveness of the Artpop Project Based Learning Method with the Literacy Room Learning Method - Ilmatus Sa’diyah; Adelia Savitri; Anas Ahmadi; Galuh Fitri Retnosari; Suvriati Vivka Merdana; Nine Alvariqati Varqa A. (Future Science, 2023)
The project-based learning method is a learning method that is considered to provide more learning experiences than other learning methods, such as discussions and lectures in class. In addition, project-based methods can also provide effective learning outcomes. In learning to write articles, both scientific articles and popular articles, a project-based learning method is needed that can improve students' writing skills. For this reason, in writing scientific articles the